ANALISIS KOSAKATA KEKUASAAN DALAM PIDATO MENDIKBUDRISTEK - Apyunita, Devi; Yustina, Ade; Mardatillah, Rahmi; Ilham, Ilham (Manifestasi: Jurnal Pendidikan dan Pengajaran, 2024)
AbstrakThis research uses a critical discourse analysis (AWK) approach with a focus on relational values in vocabulary choices, especially those related to power, through the perspective of Norman Fairclough's theory of social change. In this case, analysis was carried out on the vocabulary that describes power in texts produced by the Minister of Education and Culture with an emphasis on elements such as words, clauses and sentences. The data obtained includes documentation, reading and recording techniques that enable researchers to explore hidden meanings in the use of the vocabulary of power. The research results show that there are distinctive characteristics in the use of vocabulary related to power, such as the dominance of more striking formal words and the use of euphemisms that function to manipulate influence and power in speech. Text production and sociocultural analysis also highlight that every discourse produced cannot be separated from the context of power and domination inherent in a larger social situation. This illustrates how power influences the formation and understanding of texts, as well as showing how power is articulated in various vocabulary choices.Kata Kunci: Nilai relasional, kosakata, analisis wacana.